Clinical management of epileptic encephalopathies of childhood and infancy. (June 2014) - Covanis, Athanasios
Abstract : Epileptic encephalopathies represent a group of devastating epileptic disorders that appear early in life and are characterized by pharmacoresistant generalized or focal seizures, persistent severe EEG abnormalities, and cognitive dysfunction or decline. The ictal and interictal epileptic discharges are age-specific and are either the main cause or contribute to cognitive deterioration in the idiopathic or symptomatic group respectively. Despite choosing the most appropriate anti-seizure drugs for the seizure-type and syndrome the results are often disappointing and polytherapy and/or alternative therapy becomes unavoidable. In those cases, consideration should be given to the quality of life of the child and carers. In this review we will discuss the clinical and EEG characteristics, evolution and management of age-related epileptic encephalopathies, recognized by the International League Against Epilepsy.